A estação do neolítico antigo do Carrascal (Oeiras): resultados das escavações realizadas - Cardoso, João Luís (2021)
The exhaustive study of the evolved Early Neolithic (ca. 5300-5000 cal BC) site of Carrascal (Oeiras) is presented, encompassing the various aspects of the archaeological record represented in it. Based on the results obtained, it is possible to conclude by a stable and peri-annual human presence, where the main economic activity would be centered on the exploitation of the Cretaceous flint benches, very abundant in the location of the station andin its surroundings.